The story of Ayub in Ayub 2:1-10 and its relevance in facing life's trials - Pays, Ordiana Martha; Tanono, Solly Rosalia; Faot, Ormiaty; Taek, Delni; Maukari, Marsela; Djawa, Maya (JUPE : Jurnal Pendidikan Mandala, 2025)
The story of Job in Job 2:1-10 and its relevance in facing life's trials. The aim of this research is to understand whether Job’s life experience can be a weapon for us to face life’s trials today. The research method used in this research is the theme of the story of Job in Job 2:1-10 and its relevance in facing life’s trials. Life tests are a series of challenges and trials that we face in the course of our lives, because humans are God’s most perfect creatures and are destined to face various life tests. When facing suffering or trials in Christian life today, the character of Job becomes an inspiration for those who face difficult and unexplainable situations. This suffering ultimately led to a deeper understanding of God as stated by Job himself. Despite experiencing tremendous loss, Job remained steadfast in his faith in God.  His attitude of choosing to surrender himself to God’s existence and trust in His better plans is an inspiration for believers today to remain strong in their faith when facing suffering. Suffering is not a sign that someone has been forgotten or punished by God, but is part of a test of faith that shapes character and increases spiritual maturity.The story of Job, Job 2:1-10, Reflection on life today.